Mapping of c-Fos Expression in Rat Brain Sub/Regions Following Chronic Social Isolation: Effective Treatments of Olanzapine, Clozapine or Fluoxetine - Andrijana Stanisavljević Ilić; Dragana Filipović (Pharmaceuticals)
The c-Fos as a marker of cell activation is used to identify brain regions involved in stimuli processing. This review summarizes a pattern of c-Fos immunoreactivity and the overlapping brain sub/regions which may provide hints for the identification of neural circuits that underlie depressive- and anxiety-like behaviors of adult male rats following three and six weeks of chronic social isolation (CSIS), relative to controls, as well as the antipsychotic-like effects of olanzapine (Olz), and clozapine (Clz), and the antidepressant-like effect of fluoxetine (Flx) in CSIS relative to CSIS alone. Additionally, drug-treated controls relative to control rats were also characterized. The overlapping rat brain sub/regions with increased expression of c-Fos immunoreactivity following three or six weeks of CSIS were the retrosplenial granular cortex, c subregion, retrosplenial dysgranular cortex, dorsal dentate gyrus, paraventricular nucleus of the thalamus (posterior part, PVP), lateral/basolateral (LA/BL) complex of the amygdala, caudate putamen, and nucleus accumbens shell. Increased activity of the nucleus accumbens core following exposure of CSIS rats either to Olz, Clz, and Flx treatments was found, whereas these treatments in controls activated the LA/BL complex of the amygdala and PVP. We also outline sub/regions that might represent potential neuroanatomical targets for the aforementioned antipsychotics or antidepressant treatments.